A taxonomic revision of the Quadrideres simplicipes species-group (Coleoptera: Tenebrionidae: Pedinini), including description of a new species from Tanzania - Kamiński, Marcin Jan (Zootaxa, 2015)
The taxonomic and distributional data concerning the representatives of the Quadrideres simplicipes species-group is revised. Selinus parallelus Ancey, 1877, considered by some previous authors as incertae sedis Platynotina species, is transferred to the genus Quadrideres. Q. ruandanus Koch, 1956 is proposed as a synonym of S. parallelus. Lectotypes for Selinus parallelus, S. simplicipes Gebien, 1910, Q. robynsi Koch, 1956 and Q. ruandanus are designated to fix the taxonomic status of these species. Q. kazimierzi sp. nov. is described as a new species. An identification key is provided to all known species of the Q. simplicipes species-group. This paper brings the total species number within the genus Quadrideres to 20.